+0  
 
0
817
2
avatar

what does -y>x+1     

 Jan 7, 2016
edited by Guest  Jan 7, 2016
edited by Guest  Jan 7, 2016

Best Answer 

 #1
avatar+1904 
+5

\(-y≥x+1\)

 

\(y≤\frac{x+1}{-1}\)

 

\(y≤-\frac{x+1}{1}\)

 

\(y≤-(x+1)\)

 

\(y≤-x-1\)

 

This is what the graph looks lile: https://www.desmos.com/calculator/5b51b1qtdj

.
 Jan 7, 2016
edited by gibsonj338  Jan 7, 2016
 #1
avatar+1904 
+5
Best Answer

\(-y≥x+1\)

 

\(y≤\frac{x+1}{-1}\)

 

\(y≤-\frac{x+1}{1}\)

 

\(y≤-(x+1)\)

 

\(y≤-x-1\)

 

This is what the graph looks lile: https://www.desmos.com/calculator/5b51b1qtdj

gibsonj338 Jan 7, 2016
edited by gibsonj338  Jan 7, 2016
 #2
avatar+109518 
0

That is a terrific answer thanks gibsonj338   laugh

 Jan 8, 2016

16 Online Users

avatar
avatar